Answer:
f(1) + g(2) = 7
Explanation:
Given functions:
![\begin{cases}f(x)=-x^2+2x-3\\g(x)=10-(1)/(2)x \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/8cuq31he9txs12vsm51bg4o3fz7m08lfs2.png)
To find f(1), substitute x = 1 into function f(x):
![\begin{aligned}x=1 \implies f(1)& =-(1)^2+2(1)-3\\& = -1+2-3\\&=1-3\\&=-2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/nl51rs6safwmm4rs0xmjcb64nxz7qhp1g9.png)
To find g(2), substitute x = 2 into function g(x):
![\begin{aligned}x=2 \implies g(2)& =10-(1)/(2)(2)\\& =10-1\\&=9\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/ijvcae6l587ywvsaer2xhoprab5ooqvuoi.png)
Therefore, to evaluate f(1) + g(2), sum the two values found for f(1) and g(2):
![\begin{aligned}\implies f(1)+g(2)&=-2+9\\&=7\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/5eqymvwv8sdy3roapqx23koyvn9hqahjrp.png)
As one calculation:
![\begin{aligned}\implies f(1)+g(2)&=-(1)^2+2(1)-3+10-(1)/(2)(2)\\&=-1+2-3+10-1\\&=1-3+10-1\\&=-2+10-1\\&=8-1\\&=7\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/u7i2jsuybjrax0a28r4znjjzkcz0gqrkb2.png)